Polymorphism of tmprss2 (rs12329760) but not ace2 (rs4240157), tmprss11a (rs353163) and cd147 (rs8259) is associated with the severity of COVID-19 in the Ukrainian population - Kaidashev, Igor; Izmailova, Olga; Shlykova, Oksana; Kabaliei, Alina; Vatsenko, Anastasia; Ivashchenko, Dmytro; Dudchenko, Maksym; Volianskyi, Andrii; Zelinskyy, Gennadiy; Koval, Tetiana; Dittmer, Ulf (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Angiotensin-converting enzyme 2 (ACE2), transmembrane serine 2 and serine 11A proteases (TMPRSS2, TMPRSS11A), and a cell surface cluster of differentiation 147 (CD147) might be a gene candidate that exerts the susceptibility to and mortality from coronavirus disease 19 (COVID-19). The aim of this study was to investigate the associations between ace2, tmprss2, tmprss11a, and cd147 polymorphic variants and the severity of COVID-19 in the Ukrainian population. Methods: The study population consisted of the Ukrainian population with COVID-19: patients without oxygen therapy (n=62), with non-invasive (n=92) and invasive (n=35) oxygen therapy, as well as control subjects (n=92). Allelic polymorphisms of ace2 rs4240157, tmprss2 rs12329760, and tmprss11a rs353163 were determined by real-time PCR, and cd147 rs8259 polymorphism was detected by PCR with subsequent restrictase analysis. We compared investigated polymorphisms distribution with other populations by meta-analysis. Results: Our study is the first to obtain data about the distribution of investigated gene polymorphisms in the Ukrainian population: tmprss2 rs12329760 – CC 60.9%, CT 35.9%, TT 3.2%; tmprss11a rs353163 – CC 46.7%, CT 40.2%, TT 13.1%; ace2 rs4240157 – CC 7.6%, C 18.5%, CT 22.8%, TT 19.6%, T 31.5%; cd147 rs8259 – TT 60.9%, AT 32.6%, AA 6.5%. This distribution was similar to the Northern, Western and Southern European populations. There was a statistically significant difference in the frequency of tmprss2 polymorphic genotypes CC 57.1%, CT 28.6%, and TT 14.3% (P<0.05) in COVID-19 patients with invasive oxygen therapy in comparison with non-invasive oxygen therapy. This tmprss2 mutation occurs in the scavenger receptor cysteine-rich (SRCR) domain and might be important for protein-protein interaction in a calcium-dependent manner. Conclusions: Our study indicated the presence of an association between the tmprss2 rs12329760 polymorphism and the severity of COVID-19 in the Ukrainian population.